EVALUATION OF ANTIMICROBIAL STUDIES ON ROOT OF CARMONA RETUSA (VAHL) MASAM - Mageswari, S.; Karpagam, S. (International Journal of Current Pharmaceutical Research, 2015)
Objective: The evaluation of antimicrobial activity was carried to study the effect of root extract of Carmona retusa (Vahl.) Masam. Methods: The antimicrobial studies were carried out by using the cup plate method and the MIC was also determined. The microbial typed cultures namely Bacillus cereus, Bacillus subtilis, Enterobacter aerogens, Escherichia coli, Klebsiella pneumonia, Pseudomonas aeruginosa, Pseudomonas putida, Staphylococcus aureus, Salmonella typhimurium and Candida albicans were used. Results: The root extracts of both chloroform and alcohol showed promising activity against Bacillus subtilis (26 mm), Bacillus cereus and Candida albicans (24 mm), Pseudomonas putida and Staphylococcus aureus (20 mm) and Escherichia coli (18 mm). Conclusion: The study revealed that the antimicrobial activity of alcohol extract is comparatively higher than the chloroform extract.